2000
DOI: 10.1021/es0000753
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in the Isotope Signature of Air-Borne Sulfur in Central Europe

Abstract: In various parts of the Northern hemisphere air-borne S exhibits a seasonality, with isotopically light (i.e., 32S-rich) sulfur predominating in the warm summer months. Such seasonality has been reported from the United States, Canada, Japan, and China. Elevated biological emissions of isotopically light S in summer, a temperature-dependent isotope fractionation accompanying the oxidation of SO2, and heavy rains in winter bringing 34S-rich marine S have been suggested as the controlling mechanisms. In the atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 30 publications
6
61
1
3
Order By: Relevance
“…Even a fractionation factor of 1.07 rather than 1.14 is significantly larger than the variation observed in atmospheric samples (e.g. Norman et al (2006); Novak et al (2001)), so it is likely that RRKM theory can accurately predict only the direction and not the magnitude of this isotope effect. This is in agreement with recent results from Lin et al (2011) and Hattori et al (2011), which found a similar overprediction of the sulfur isotopic fractionation during the photolysis of OCS by RRKM theory (Leung et al, 2002).…”
Section: Isotopic Fractionation During the Gas-phase Oxidation Of So mentioning
confidence: 97%
See 3 more Smart Citations
“…Even a fractionation factor of 1.07 rather than 1.14 is significantly larger than the variation observed in atmospheric samples (e.g. Norman et al (2006); Novak et al (2001)), so it is likely that RRKM theory can accurately predict only the direction and not the magnitude of this isotope effect. This is in agreement with recent results from Lin et al (2011) and Hattori et al (2011), which found a similar overprediction of the sulfur isotopic fractionation during the photolysis of OCS by RRKM theory (Leung et al, 2002).…”
Section: Isotopic Fractionation During the Gas-phase Oxidation Of So mentioning
confidence: 97%
“…Seasonality in data, with lower δ 34 S values measured for sulfate in summer, could show that the gas-phase fractionation factor is less than the heterogeneous fractionation factor and probably less than 1 (Saltzman et al, 1983;Sinha et al, 2008a). However, seasonality may also be explained by changing sources or the temperature-dependence of fractionation factors (Caron et al, 1986;Novak et al, 2001;Ohizumi et al, 1997). The study of 17 O of sulfate trapped in ice cores showed that the ratio of gas-phase to aqueous-phase oxidation was higher and the δ 34 S was lower during the last glacial maximum than the preceeding and subsequent interglacials (Alexander et al, 2002(Alexander et al, , 2003.…”
Section: Sulfur Isotopes In the Environmentmentioning
confidence: 98%
See 2 more Smart Citations
“…[4] Sulfur isotopes have been traditionally used to identify and characterize the sources of sulfur in the atmosphere because sources such as anthropogenic SO 2 , biogenic sulfur, and sulfur from airborne particulate matter (dust and mineral matter) often possesses different d 34 S values [Nielsen, 1974;Kawamura et al, 2001;Norman et al, 1999;Novak et al, 2001;Ono et al, 2009;Lyons, 2009;Szynkiewicz et al, 2009]. The sulfur isotopes in atmospheric aerosols over China have been observed to be similar to those in coal combusted in the region [Mukai et al, 2001].…”
Section: Introductionmentioning
confidence: 99%